Keterbukaan Informasi Hak Guna Usaha pada Badan Usaha Milik Negara: Rekonstruksi Regulasi untuk Kepastian Hukum dan Akuntabilitas Agraria: Public Information Disclosure of Cultivation Rights in State-Owned Enterprises: Regulatory Reconstruction for Legal Certainty and Agrarian Accountability - Maftuha Kiswah; Deva Alfianto Supardi (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2026)
The governance of the Right to Cultivate (HGU) in Indonesia, particularly within State-Owned Enterprises (SOEs) and Regional-Owned Enterprises (ROEs), is directly related to state finances. Limited access to HGU documents risks impeding accountability and triggering agrarian conflicts. This study aims to analyze the legal framework of HGU governance in SOEs/ROEs and to formulate a reconstruction of HGU information disclosure regulations. This method used is normative juridical with statutory and case approaches. The results of the study reveal a normative disharmony between the disclosure obligations under the Public Information Disclosure Law and the absence of proactive publication mechanisms for HGU data. The main finding showd thet the evaluation of HGU governance must be based on Article 80 of Government Regulation Number 18/2021 and the community plantation obligation of 20 percent, as well as requiring a distinction of three categories of HGU information. This reconstruction can be implemented through a Joint Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency and the Head of the SOE Regulatory Agency. This article proposes a novel three-tier disclosure model distinguishing core HGU information, compliance information, and commercially sensitive information, addressing the existing regulatory gap at the intersection of agrarian law, state finance law, and public information law.